HEPATIC METASTATIC MENINGIOMA FOLLOWING REPEATED INTRACRANIAL REMOVAL SURGERIES : Hepatic Metastatic Meningioma - Audrey Clarissa; Tiara Aninditha; Eka Susanto; Kemal Fariz Kalista; David Tandian; Irma Savitri Madjid; Henry Riyanto Sofyan (Acta Neurologica Indonesia, 2025)
Introduction : Meningioma is mostly benign. With appropriate management, it may have a good prognosis. However, it may reoccur and metastasize in <1% of all cases. Studies describing re-occurrences of meningioma and extracranial metastasis, especially to the liver, are limited. Case Report : A 54-year-old female with secondary headache, cognitive impairment, blindness in the left eye, and paresis of the left facial nerve due to recurrent left spheno-orbital meningioma with scalp invasion had undergone four tumor removal surgeries. Previous histopathological findings were atypical meningioma (2017) and transitional meningioma (2023). A suspicion of a new primary tumor arose as an increase in transaminase and multiple liver nodules were observed despite being an asymptomatic patient. Histology and immuno-histochemistry from the intracranial tumor was an atypical meningioma, and cancer in the liver had a similar immunohistochemistry profile as the intracranial tumor, suggesting meningioma metastasis. Discussion : Recurrences were more prevalent in higher histologic grading, which can lead to serial operations, higher complication rates, and morbidities. While the lungs are the most common site for metastasis, hepatic metastasis is thought to be underestimated as patients are often asymptomatic. Factors such as scalp and brain invasion, blood vessel proximity, meningioma recurrences, and subtotal resection increase the risk of metastasis. To date, there are no specific guidelines on metastasis treatment. Conclusion : Meningioma can re-occur and metastasize to distant organs despite its usual benign characteristics. Aggressive tracking should be implemented in females with recurrent meningioma and scalp involvement